ACP+: An Age Control Protocol for the Internet - Shreedhar, Tanya; Kaul, Sanjit K.; Yates, Roy D. (IEEE/ACM transactions on networking, 2024)
We present the age control protocol ACP+, a transport layer protocol that regulates the rate at which update packets carrying information from a source are sent over the Internet to a monitor. The source would like to minimize the average age of information at the monitor. Extensive experimentation helps shed light on age control over the current Internet and its implications for sources sending updates over a shared wireless access to monitors in the cloud. Surprisingly, age minimizing rates over fast Internet paths are about 0.5 Mbps, which is a small fraction, for example, of link rates supported by WiFi wireless access technology. We also show that congestion control algorithms employed by the Transmission Control Protocol (TCP), including hybrid approaches that achieve higher throughputs at lower delays than traditional loss-based congestion control, are unsuitable for age control.